EKSPLORASI PUISI “AKU” KARYA CHAIRIL ANWAR MELALUI MODEL EKSPRESIF PENDEKATAN ABRAMS: RELASI PENYAIR, KARYA, DAN SEMESTA - Kasrani, Meliawati Rizki; Rahmah, Adnin Fauziyah; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study attempts to explore more deeply the poem "Aku" by Chairil Anwar through an expressive approach introduced by M.H. Abrams. In this approach, literary works are understood as a direct reflection of the poet's soul closely related to life experiences, emotions, and his perspective on the world. The poem "Aku" was chosen because it is one of Chairil Anwar's most iconic works that expresses the spirit of individualism, resistance, and the search for identity. By using qualitative methods and a descriptive-analytical approach. The results of the exploration show that this poem is a strong self-expression and describes the poet's desire to live freely and not be bound by social norms or time constraints. This poem represents the poet's strength and resilience in facing difficulties and wounds, as well as the rejection of social norms that limit individual freedom.